UI/UX Design of Web-based Software License Management System using User-Centered Design and System Usability Scale - Faizah, Ovie Nur; Oktadini, Nabila Rizky; Putra, Bayu Wijaya; Sevtiyuni, Putri Eka; Putra, Pacu; Meiriza, Allsela (Jurnal Nasional Teknologi dan Sistem Informasi, 2023)
PT Bukit Asam Tbk (PTBA), a state-owned coal mining company, must comply with government regulations regarding software licenses. They face difficulties monitoring and managing licenses that could lead to violations. To solve this problem, we try to design a website-based UI/UX for Software License Management System. This research aims to provide an intuitive interface and a comfortable user experience employing the User-Centered Design (UCD) approach, which consists of three main stages: Needs Analysis, Design and Prototyping, and Evaluation. Evaluation is carried out through usability testing using the System Usability Scale (SUS). Test results indicate that UCD is effective in designing a system responsive to user needs with a high level of usability. With an effectiveness of 99%, efficiency of 96.67%, and an SUS score of 88.25, this system design receives an 'Acceptable' rating, a (B) grade, and falls into the 'Excellent' category. The designed system is deemed suitable for further development towards the implementation phase.